Overlapping organizations, political crises, and coexistence: complementarity and fragmentation in south american and african regionalisms - Ribeiro, Clarissa Correa Neto [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The present research has the occurrence of overlapping regionalisms as its object, with a comparative cut for South America and Africa. The purpose of this thesis is to study types of institutional interaction and to analyze the effects of overlapping in the coexistence between regional processes in order to understand their dynamics in the above-mentioned regions. The observation of organizational behaviors and interaction is made through cases of political crises on the selected regions, as we assume that the interactions between overlapping regional organizations in those situations would tend to be more fragmenting than complementary as they go beyond the traditional membership-mandate relationship. Therefore, we also analyze overlapping performances and seek to understand how regional organizations will behave and interact while dealing with political crises, which constitute critical junctures, in accordance with the theoretical and methodological framework of the thesis. This work aims to produce a broad qualitative analysis of the given regions by considering applicable cases that cover all of the sub-regions and hence to contribute to the field of comparative regionalism by providing generalization and institutional learnings which are not derived by a given model of regionalism, but nonetheless based on a cross regional approach. The data is processed through document analysis and further systemized via the construction of presence and absence exercises, consisting on testing of hypotheses and dyadic relationships.

A presente pesquisa tem por objeto a ocorrência de regionalismos sobrepostos, com recorte comparativo para a América do Sul e a África. O propósito desta tese é estudar tipos de interação institucional e analisar os efeitos da sobreposição na coexistência entre processos regionais, de modo a entender sua dinâmica nas regiões supramencionadas. A observação de comportamentos organizacionais e interações é feita através de casos de crises políticas nas regiões selecionadas, uma vez que se assume que ditas interações entre organizações regionais sobrepostas tenderiam a produzir efeitos mais fragmentantes do que complementares para o espaço, uma vez que as mesmas ultrapassam a tradicional relação entre filiação e mandato. Portanto, se analisa também a sobreposição de performances enquanto se procura compreender como as organizações regionais irão se comportar e interagir ao lidar com crises políticas, que constituem conjunturas críticas, de acordo com o referencial teóricometodológico da pesquisa. A tese pretende produzir uma análise qualitativa de grande dimensão das regiões dadas, considerando casos aplicáveis que abarquem todas as sub-regiões e, assim, contribuir para o campo do regionalismo comparado, fornecendo generalizações e aprendizagens institucionais que não são derivadas de um dado modelo de regionalismo, mas, baseadas em uma abordagem regional cruzada. Os dados são processados através da análise de documentos e posteriormente sistematizados através da construção de exercícios de presença e ausência, consistindo no teste de hipóteses e relações diádicas.

La presente investigación tiene como objeto la superposición de regionalismos como su objetivo, con un corte comparativo para América del Sur y África. El objetivo de esta tesis es estudiar los tipos de interacción institucional y analizar los efectos de la superposición en la coexistencia entre procesos regionales para comprender su dinámica en las regiones mencionadas. El objetivo de esta tesis es estudiar los tipos de interacción institucional y analizar los efectos de la superposición en la coexistencia entre procesos regionales para comprender su dinámica en las regiones mencionadas. La observación de los comportamientos e interacciones organizacionales se realiza a través de casos de crisis políticas en las regiones seleccionadas, ya que suponemos que las interacciones entre las organizaciones regionales superpuestas en esas situaciones tenderían a ser más fragmentarias que complementarias, ya que van más allá de la relación tradicional de membresía-mandato. Por lo tanto, también analizamos desempeños superpuestos y buscamos comprender cómo se comportarán e interactuarán las organizaciones regionales al enfrentar crisis políticas, que constituyen coyunturas críticas, de acuerdo con el marco teórico y metodológico de la tesis. La tesis tiene como objetivo producir un análisis cualitativo amplio de las regiones dadas al considerar los casos aplicables que cubren todas las subregiones y, por lo tanto, contribuir al campo del regionalismo comparativo al proporcionar generalizaciones y aprendizajes institucionales que no se derivan de un determinado modelo de regionalismo, pero basado en un enfoque regional cruzado. Los datos se procesan a través del análisis de documentos y se sistematizan aún más mediante la construcción de ejercicios de presencia y ausencia, que consisten en la prueba de hipótesis y relaciones diádicas.
Sobreposições organizacionais, crises políticas e coexistência: complementaridade e fragmentação nos regionalismos sul-americano e africano
Keywords: Regionalism; Overlapping organizations; Regional integration; South America; Africa; Political crises; Democracy protection; Regionalismo; Organizações sobrepostas; Integração regional; América do Sul; Crises políticas; Proteção democrática; Organizaciones superpuestas; Integración regional; Sudamerica; Crisis políticas; Protección democrática